Современные особенности и тенденции участия стран с формирующимся рынком на мировом рынке капитала (Путеводитель предпринимателя, 2020)
This article is focused on the participation of emerging market economies in the international capital market. The author analyses the recent trends of international capital flows as well as specifies the threats of capital inflows to borrowing countries.